Find the maximum clique by graph coloring using heuristic greedy - Mustafa, Mamat; Suyudi, .; Sukono, .; Bon, A.T. (2019)
Graph coloring problem is to find the minimal number of colors to color vertex of a graph in such a way that every two vertex linked by an edge have different colors. A vertex coloring algorithm has been presented. As a result of applying vertex coloring algorithm no two vertex are to be allocated in same color if they are adjacent in graph. In this paper, Graph coloring used for to find maximum clique in a graph with heuristic greedy